2014
DOI: 10.5897/ajar2013.6935
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of smallholder commercialization of horticultural crops in Gemechis District, West Hararghe Zone, Ethiopia

Abstract: Transforming the subsistence-oriented production system into a market-oriented production system as a way to increase the smallholder farmer's income and reduce rural poverty has been in the policy spotlight of many developing countries, including Ethiopia. However, there are no adequate studies in Ethiopia, particularly, in study area of West Hararghe zone that focusing on the determinants of smallholder commercialization in horticultural crops. This study has identified household level determinants of the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 6 publications
4
19
0
Order By: Relevance
“…As size of land allocated to mango increased by one hectare, the amount of mango supplied to the market increased by 17.12 qt. This result was similar to the finding by Addisu (2016) and Aman et al (2014) who found that the size of land allocated for horticultural crops and potato, respectively increased quantity of produce available for sale.…”
Section: Sex Of Household Headsupporting
confidence: 90%
“…As size of land allocated to mango increased by one hectare, the amount of mango supplied to the market increased by 17.12 qt. This result was similar to the finding by Addisu (2016) and Aman et al (2014) who found that the size of land allocated for horticultural crops and potato, respectively increased quantity of produce available for sale.…”
Section: Sex Of Household Headsupporting
confidence: 90%
“…An increase in market distance by 1km decreases the level of teff commercialization by 0.36% or 0.0036. This finding is confirmed with the study conducted by Aman et al (2014) and Solomon et al (2010) who found that being closer to the market enhanced market participation.…”
Section: Distance From the District Marketsupporting
confidence: 88%
“…The marginal effect shows that keeping all other factors constant, the probability of household's market participation decreases by 16.8% as the size of the family size increases by one person. stated that as the number of household member increases more, the probability of household's market participation decreases more hence they consume fruit more (Tufa et al, 2014). In other way round, the level of household market participation in selling of fruits decreases when the number of months to be feed increases, and disproportionate volume of production provided.…”
Section: Determinants Of Smallholder's Participation Decision In Commmentioning
confidence: 99%
“…This indicates that as farmers are more near to the market place their participation in fruit marketing becomes increasing hence fruits are easily putrefied from too far. The degree of commercializing fruits increases as the distance of market from farmer's residence is too small (Tufa et al, 2014). Ogunleye and Oladeji (2007) pointed out that the extent of farmer's market participations is hampered by a greater distance to the market.…”
Section: Determinants Of Smallholder's Participation Decision In Commmentioning
confidence: 99%